Strategi Terintegrasi untuk Pengelolaan Kawasan Cagar Budaya di Kota Surakarta - Pratomo Aji Krisnugrahanto; Denny Zulkaidi (KALPATARU, 2020)
Abstract. Every cultural heritage has different strategic management depends on its context. This research focused on the lack of good management strategy for Cultural Heritage Area in Surakarta City. The aims of this study is to formulate an integrated strategic management for cultural heritage areas in Surakarta City. This research used qualitative exploratory methodology with inductive approach. Primary data were obtained from field observations and interviews with sources related to cultural preservations, while secondary data were obtained from Surakarta City planning documents. The strategic management aimed for the community and government, therefore the internal variable is the condition of four aspects strategic management owned by the community and the city government, while the external variable is from outside the community and the city government. This research produces 73 strategy formulations which are summarized into 43 formulations based on the predicated similarity. The designation of strategy for managing Cultural Heritage Area is divided into two parts, which are 13 strategies for the scale of Surakarta City and 30 strategies for each region. Management integration can be seen from these strategies that are divided into each aspect to support the management of Cultural Heritage Area in Surakarta City. Keywords: Strategic Management, Cultural Heritage Area, Surakarta City Abstrak. Setiap cagar budaya membutuhkan strategi pengelolaan yang berbeda sesuai dengan konteks cagar budaya. Keberadaan bangunan dan kawasan cagar budaya menjadi permasalahan tersendiri bagi perkembangan kota Surakarta. Sampai saat ini, kota Surakarta belum memiliki strategi pengelolaan kawasan cagar budaya yang terintegrasi. Penelitian ini merumuskan strategi pengelolaan kawasan cagar budaya yang terintegrasi di kota Surakarta. Metode penelitian yang digunakan adalah eksploratif kualitatif dengan pendekatan induktif. Data primer diperoleh dari observasi KCB dan wawancara dengan narasumber terkait cagar budaya, sedangkan data sekunder diperoleh dari dokumen perencanaan kota Surakarta. Strategi pengelolaan ditujukan masyarakat dan Pemerintah Kota Surakarta sehingga variabel internal adalah kondisi aspek strategi pengelolaan yang dimiliki masyarakat dan pemerintah kota, sedangkan variabel eksternal adalah kondisi aspek strategi pengelolaan dari luar masyarakat dan pemerintah kota. Penelitian ini menghasilkan 73 rumusan strategi yang kemudian diringkas menjadi 43 rumusan berdasarkan kesamaan predikat dan makna. Peruntukan strategi terbagi dalam 13 strategi pengelolaan kawasan cagar budaya untuk skala kota Surakarta, 30 strategi pengelolaan kawasan cagar budaya untuk setiap kawasan. Integrasi pengelolaan dapat diketahui dari adanya 17 strategi yang merupakan ringkasan dari 43 strategi dan digolongkan sesuai aspek pengelolaan kawasan cagar budaya. Kata kunci: Strategi Pengelolaan, Kawasan Cagar Budaya, Kota Surakarta